PENGARUH KADAR PEREKAT RESIN PADA SIFAT FISIS DAN MEKANIS PADA SPESIMEN DENGAN BAHAN SERBUK HALUS ENCENG GONDOK - Nuzuli Fitriadi; Fadli A Kurniawan (J-Innovation, 2015)
Water hyacinth is one of the agricultural commodities that contain elements of lignocellulose so that a potential raw material in the manufacture of composite materials because growth is relatively fast and very easy to obtain. The purpose of this study is to make a fine powder composite specimen water hyacinth 10%, 20% and 30%, and find the value of the mechanical characteristics of the composite specimen fine powder of water hyacinth to perform tensile strength using testing standard ASTM D638M-84. Specimens were made with the simplest method (hand lay up). Furthermore, the composite was left for approximately 24 hours so that the results are as expected. From the tensile test results obtained by the value of the average voltage 14.987 KPa, average of 3.804 strain, and modulus of elasticity average 442.8 KPa. It is known that the higher the percentage of the fine powder of the resin, the higher value of tensile strength and modulus of elasticity.